Free vibration of functionally graded sandwich plates with stiffeners based on the third-order shear deformation theory - Dat, Pham Tien; Thom, Do Van; Luat, Doan Trac (Vietnam Journal of Mechanics, 2016)
In this paper, the free vibration of functionally sandwich grades plates with stiffeners is investigated by using the finite element method. The material properties are assumed to be graded in the thickness direction by a power-law distribution. Based on the third-order shear deformation theory, the governing equations of motion are derived from the Hamilton’s principle. A parametric study is carried out to highlight the effect of material distribution, stiffener parameters on the free vibration characteristics of the plates.